2009
DOI: 10.1007/s11119-009-9112-6
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of precision farming in Germany: acceptance, adoption, obstacles, knowledge transfer and training activities

Abstract: The adoption of precision farming (PF) was studied on the basis of personal interviews conducted at several agricultural exhibitions in Germany. Between 6.65% and 11% of the interviewed farmers used PF. The majority used data collection techniques such as GPS-based area measurement and soil sampling rather than variable rate application techniques such as site-specific sowing and fertilising. Roughly half the farmers interviewed knew about PF. About 7-10% of them intended to start using PF in the future. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 10 publications
(19 reference statements)
3
37
0
Order By: Relevance
“…One major driver mentioned as important by almost all publications is the quality of support [68,69,73,74,79,81,84,[109][110][111][112][113][114][115]. Reichardt et al [68] declared that farmers need more information about the different farming tools and more training opportunities as well as a better advisory service.…”
Section: Drivers For Disruptive Innovations Of Other Typesmentioning
confidence: 99%
See 2 more Smart Citations
“…One major driver mentioned as important by almost all publications is the quality of support [68,69,73,74,79,81,84,[109][110][111][112][113][114][115]. Reichardt et al [68] declared that farmers need more information about the different farming tools and more training opportunities as well as a better advisory service.…”
Section: Drivers For Disruptive Innovations Of Other Typesmentioning
confidence: 99%
“…Reichardt et al [68] declared that farmers need more information about the different farming tools and more training opportunities as well as a better advisory service. Watcharaanantapong et al [69] even observed that farmers who obtained farming information from farm dealers, crop consultants, university extension, other farmers, trade shows, the internet, and/or news media were more likely to adopt complex disruptive innovations.…”
Section: Drivers For Disruptive Innovations Of Other Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…The interest to invest in such implements and to change the necessary management decisions, varies between farmers. Reichardt et al (2009) interviewed farmers (in Germany) regularly about their knowledge and adoption status and found the need for better information, e.g. in education, and that only parts of the farmers are introducing precision technology.…”
Section: Site-specific Weed Managementmentioning
confidence: 99%
“…There is a number of studies that surveyed a variety of factors (socio-economic, agro-ecological, institutional, technological or behavioral), which affect the uptake of PA technology by farmers [2,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%